Electrochemical Study of Ellipticine Interaction with Single and Double Stranded Oligonucleotides - Tmejova, Katerina; Krejcova, Ludmila; Hynek, David; Adam, Vojtech; Babula, Petr; Trnkova, Libuse; Stiborova, Marie; Eckschlager, Tomas; Kizek, Rene (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Ellipticine (5,11-dimethyl-6H-pyrido[4,3-b]carbazole) is an alkaloid that has been isolated from plants of an Apocynaceae family. It is one of the simplest naturally occurring alkaloids with a planar structure. Over the past decades, ellipticine became a very promising antitumor agent. Interaction with DNA is one of the most studied ellipticine effects on cell division. This phenomenon is not clearly explained so far. In our experiments we studied interaction of ellipticine with single-stranded and double-stranded oligonucleotides by electrochemical methods on mercury electrode. Differential pulse voltammetry was applied for ellipticine (Elli) and CA peak detection. Square wave voltammetry was applied for G peak detection. The effect of the interaction time and ellipticine concentrations on interactions of ellipticine with single- and double-stranded oligonucleotides was tested too.
Keywords: square wave voltammetry